Neurofibromatosis type 1 with combined mutation. - Mun, A.V.; Kuddusova, K.K.q. (European Journal of Pediatric Dermatology, 2024)
Neurofibromatosis is a frequent autosomal dominant inherited skin disorder caused by a pathogenic variant of the NF1 gene. An exceptional case is presented in an 8-year-old girl who also had a probably pathogenic mutation of the IGF1R gene. The differential diagnosis of the disease and the role of genetic testing in the diagnostic process were also discussed.